Sea Level Rise and the Impact for the Port - Zikra, Muhammad; Sambodho, Kriyo; Naturezza, Defian (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2015)
The problems in port infrastructures related with climate change, especially sea level rise, have continued to receive a high level of attention. Knowledge of climate change should become a major interest for engineer, stakeholders, and decision makers or the port authorities in port industry for developing mitigation and adaptation strategies in the future. The objective of this paper is to measure sea level change in the Indonesian sea from satellite altimetry. In this study, satellite altimetry mission of Jason-2 are used to obtain altimetry data from NOAA server databse. These data are processed by using software Basic Radar Altimetry Toolbox (BRAT). Analysis of sea level change is done for 4 years period from 2009 to 2012 in 4 locations, which are Medan, Pemangkat, Ambon, and Manokwari. The results showed that the highest sea level rise is in Manokwari 14.10 mm/year, and the lowest is in Ambon with trend of sea level rise 1.17 mm/year.